Evaluation Of Smart Village Open Data To Realise Digital Village In Malang Regency - Azizatun Nafi’ah, Binti; Edo Wahyudi, Kalvin (International Journal of Science, Technology & Management, 2024)
Government policies that focus on Open Government Data (OGD) often aim to encourage the provision of interoperable public data to any user, including the lay citizen, through online portals. However, these OGD portals are mostly not updated and the portals do not yet contain data needed by the public such as performance reports, financial reports, activity reports, and other data. This condition occurs in many village governments in Malang District. Researchers focused on evaluating open data in village governments by measuring the principles of open data. Researchers collected data using interviews and observations. Researchers found that the public information disclosure score in Putukrejo village government was 55%. Putukrejo village government's public information disclosure has not been maximised because many elements have not been fulfilled such as data files that have not been uploaded including village regulations, financial reports, and other village documents; timeliness in news updates is also still not optimal; and interactive services and complaints.